Perceptions of Trans Padang bus drivers on type A terminal location case study: Anak Air type A terminal - Ashar, Faisal; Marzeki, Yuda; Rifwan, Fitra; Septiani, Nazmi (Universitas Negeri Padang, 2022)
Since the inactivity of the Bingkuang Regional Terminal in 2009, the city of Padang no longer has a bus terminal, which causes many shadow terminals in the city of Padang. In 2021, the Type A Terminal in Padang City was completed and tested immediately since not October 2021. However, since the trial until now this terminal is still quiet for buses and the public to visit. Then in 2021, the Type A Terminal in Padang City was completed and tested immediately since not October 2021. However, since the trial until now this terminal is still quiet for buses and the public to visit. Anak Air Type A Terminal is still quiet due to its location which is far from the city center, and access to the Anak Air Type A Terminal is considered quite difficult. The formulation of the problem in this study is how the perception of the Trans Padang bus driver on the location of the Anak Air Type A Terminal and the completeness of the facilities it has. The standard used in this study is the Decree of the Director General of Land Transportation No. 31 of 1995 concerning Road Transportation Terminals. The purpose of this study was to find out and provide the opinion of bus drivers on the existence of Anak Air Type A Terminal in Padang City and determine the feasibility of the Anak Aia Terminal based on the facilities it has. The method used in this research is qualitative type. The sample in this study was the Trans Padang bus driver. The data were collected by using interview techniques with Trans Padang bus drivers who enter the Anak Air Type A Terminal every day, observations at the terminal location to record the facilities that this terminal already has and documentation in the form of photographs. The results of the research that has been carried out through interviews with Trans Padang bus drivers found 3 keywords, namely the location of the terminal which is considered appropriate, access to the terminal is difficult to pass and there are still many facilities that are not yet available at Anak Air Type A Terminal.